Successful remote treatment of a client with Hikikomori using internet-delivered cognitive therapy for social anxiety disorder: a case report - Sakai, M; Yoshinaga, N; Thew, G; Clark, DM (Frontiers Media, 2024)
Hikikomori (prolonged social withdrawal) has been discussed as a hidden worldwide epidemic and a significant social and healthcare issue. Social anxiety disorder is the most common psychiatric disorder preceding the onset of Hikikomori. Although studies exist suggesting the effectiveness of family-support interventions, little is known about psychotherapeutic approaches for Hikikomori individuals. Here, we present a case of Hikikomori wherein an internet-delivered cognitive therapy for social anxiety disorder (iCT-SAD) worked effectively in improving the client’s social anxiety symptoms and social interaction behaviors. This case study demonstrates the principle that evidence-based psychological interventions focusing on social anxiety can be effective for clients with Hikikomori. Furthermore, the online mode of treatment delivery, along with a variety of relevant modules, may facilitate clients’ engagement with treatment at home. The findings suggest that iCT-SAD might be a promising option for Hikikomori clients who have social anxiety problems, within the recommended stepped-intervention approach.